Enabling Suzuki–Miyaura coupling of Lewis-basic arylboronic esters with a nonprecious metal catalyst. Issue 43 (28th October 2022) - Haibach, Michael C.; Ickes, Andrew R.; Tcyrulnikov, Sergei; Shekhar, Shashank; Monfette, Sebastien; Swiatowiec, Rafal; Kotecki, Brian J.; Wang, Jason; Wall, Amanda L.; Henry, Rodger F.; Hansen, Eric C.
Abstract : A simple inexpensive ligand enables the Ni-catalyzed Suzuki–Miyaura coupling of heterocyclic and Lewis-basic arylboronic esters under mild conditions. Abstract : The high cost and negative environmental impact of precious metal catalysts has led to increased demand for nonprecious alternatives for widely practiced reactions such as the Suzuki–Miyaura coupling (SMC). Ni-catalyzed versions of this reaction have failed to achieve high reactivity with Lewis-basic arylboron nucleophiles, especially pinacolboron esters. We describe the development of (PPh2 Me)2 NiCl2 as an inexpensive and air-stable precatalyst that addresses this challenge. Under activation by n -BuMgCl, this complex can catalyze the coupling of synthetically important heteroaryl pinacolborons with heteroaryl halides. Mildly basic conditions (aqueous K3 PO4 ) allow the reaction to tolerate sensitive functional groups that were incompatible with other Ni-SMC methods. Experimental and computational studies suggest that catalyst inhibition by substitution of PPh2 Me from Ni(ii ) intermediates by Lewis basic reactants and products is disfavored relative to more commonly employed ligands in the Ni-SMC, which allows it to operate efficiently in the presence of Lewis bases such as unhindered pyridines.